Risk management in student affairs : foundations for safety and success - Miller, Thomas E., 1948 November 25-; Sorochty, Roger W. (Jossey-Bass, 2015)
A comprehensive, accessible guide to the policies and practices of risk management in higher education Student affairs staff at all types of colleges and universities need to be equipped to help manage risk and protect their institutions, the people they serve, and their resources from unintended consequences. Risk Management in Student Affairs: Foundations for Safety and Success helps practitioners understand the sources of risk in their work, and the practices and strategies they can employ to help mitigate that risk. Written for those without legal training, the book is ac.